2018
DOI: 10.1186/s13287-018-0956-4
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived extracellular fraction characterization: biological and clinical considerations in regenerative medicine

Abstract: BackgroundAdipose tissue-derived stem cells are considered to be a promising source in the field of cell therapy and regenerative medicine. In addition to direct cell replacement using adipose tissue or purified stem cells, intercellular molecule exchange by the adipose tissue complex, a vast array of bioactive secretory factors, demonstrated beneficial effects by reducing tissue damage and stimulation of endogenous repair. However, for therapeutic purposes, the use of secretome derivatives, such as full condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 61 publications
3
83
0
1
Order By: Relevance
“…Numerous studies in recent years have demonstrated that adipose tissue has a significant impact on the cellular microenvironment by the secretion of a wide range of bioactive factors with pleiotropic functions. We previously demonstrated that adipose tissue extracellular fraction, easily isolated from lipoaspirate during intra‐operatory time, exhibits significant potential in skin repair . Here, consistent with the idea that stress‐related modification of the entire skin may be responsible for melanocytes loss and failure in repigmentation, we propose an innovative approach based on AT‐Ex to target most of the recognized defects of vitiligo skin.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Numerous studies in recent years have demonstrated that adipose tissue has a significant impact on the cellular microenvironment by the secretion of a wide range of bioactive factors with pleiotropic functions. We previously demonstrated that adipose tissue extracellular fraction, easily isolated from lipoaspirate during intra‐operatory time, exhibits significant potential in skin repair . Here, consistent with the idea that stress‐related modification of the entire skin may be responsible for melanocytes loss and failure in repigmentation, we propose an innovative approach based on AT‐Ex to target most of the recognized defects of vitiligo skin.…”
Section: Discussionsupporting
confidence: 71%
“…Levels of bFGF, SCF, ET‐1, α‐MSH and GM‐CSF are lower in vitiligo lesion in comparison with healthy control . We have recently demonstrated that SCF, α‐MSH, GM‐CSF bFGF, keratinocyte growth factor (KGF) and nerve growth factor important regulators of melanocyte biology are abundantly present in the extracellular fraction of lipoaspirates . Altogether, the AT‐Ex profile proved that it is an enriched mixture of growth factors usable in skin regeneration.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations